2017
DOI: 10.7752/jpes.2017.01056
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Abstract:Purpose: determination of physiological and subjective parameters of reaction to physical load of female basketball players with different anthropometrical parameters. Material: in the research qualifies female basketball players of age 20-22 years (n=58) participated: 17 center players (body length 188±3.2 cm); 19 wingers (body length 178±4.3 cm); 22 fullbacks (body length 169±6.5 cm). Sportswomen fulfilled work on ergo-meter with step-by-step increading load up to individual maximum. Results: the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 13 publications
4
21
1
2
Order By: Relevance
“…et al [16,17] was determined the high influence of psychophysiological functions on the efficiency of the training process of athletes. In our research, the role of psychophysiological factors in different kinds of the sport was also confirmed [18][19][20]. This is also relevant for aesthetic sports [18,21].…”
Section: Introductionsupporting
confidence: 71%
“…et al [16,17] was determined the high influence of psychophysiological functions on the efficiency of the training process of athletes. In our research, the role of psychophysiological factors in different kinds of the sport was also confirmed [18][19][20]. This is also relevant for aesthetic sports [18,21].…”
Section: Introductionsupporting
confidence: 71%
“…This indicates a highly structured work of the body in the athlete of high qualifications. Similar data were obtained by us earlier in studies of the structure of the preparedness of basketball players [12,21,22]. it was observed that with the increase in the level of sportsmanship, athletes increased the number of correlation links between different types of preparedness; there are interrelations between those indicators that have not been interconnected previously.…”
Section: Discussionsupporting
confidence: 87%
“…of particular importance is the problem associated with the maximum manifestation of physical qualities, for example, in athletics. Currently, achievements in athletics are approaching the peak of human capabilities [19,20], and the training process in the sport of higher achievements has reached the maximum values of volume and intensity of physical exertion [21,22]. Therefore, the search for ways to improve the efficiency of the training process by optimizing it without increasing the volume and intensity of the loads, and also by taking into account and applying the training factors to enhance the sporting skills is of particular relevance.…”
Section: Introductionmentioning
confidence: 99%
“…To determine the psychophysiological state of athletes during the first and last week of the experiment, psychophysiological indicators were recorded using the computer program "Psychodiagnostics" (Kozina, Iermakov, Crełu, Kadutskaya, & Sobyanin, 2017;Kozina, Prusik, Görner, Sobko, Repko, Bazilyuk, et al , 2017;Kozina, Prokopenko, Cretu, Chaika, Ryepko, Osiptsov, Razumenko, Kudryavtsev, & Polianskyi, 2018;Kozina, Kalinicenko, Cretu, Osiptsov, Kudryavtsev, Polishchuk, Ilnickaya, & Minenok, 2018). The following parameters were fixed:…”
Section: Participantsmentioning
confidence: 99%
“…(2017), the development of the coordination abilities of players ZHANNETA KOZINA, YANA GOLOBORODKO, YURII BOICHUK IRINA SOBKO, OLENA REPKO, TATYANA BAZILYUK, IRINA PROKOPENKO, IVAN PROKOPENKO, ANDRII PROKOPENKO, NATALIIA TARARAK, ANDREY OSIPTSOV, VIKTOR KOSTIUKEVYCH, ANATOLII GUBA, MIKOLA TRUBCHANINOV, ANTON POLIANSKYI, VIKTORIYA ROSTOVSKA, ANDRII DRACHUK, acquires particular urgency. At present, in the context of studies of the coordination abilities of athletes in various sports, the authors touch upon the questions of the dosage of physical exertion (Kozina, Iermakov, Crełu, Kadutskaya, & Sobyanin, 2017), the psychophysiological state (Aksoy, & Agaoglu, 2017;Galli, Cimolin, Rigoldi, Moro, Loi, & Pau, 2017;Korobeynikov, Korobeynikova, Iermakov , & Nosko, 2016;Korobeynikov, Mazmanian, Korobeynikova, & Jagiełło, 2011;Korobeynikov, Myshko, Pastukhova, & Smoliar, 2017;Kozina, Iermakov, Crełu, Kadutskaya, & Sobyanin, 2017;Kozina, Prusik, Görner, Sobko, Repko, Bazilyuk, et al, 2017), the control of the training effect (Davila, Davidson, Dahl, Bazilyuk, et al, 2017;Fleddermann, Heppe, Eils, & Zentgraf, 2016;Kozina, Prokopenko, Cretu, Chaika, Ryepko, Osiptsov, Razumenko, Kudryavtsev, & Polianskyi, 2018;Davila-Romero, Hernandez-Mocholi, & Garcia-Hermoso, 2015;Gjinovci, Idrizovic, Uljevic, & Sekulic, 2017;Kozina, Kalinicenko, Cretu, Osiptsov, Kudryavtsev, Polishchuk, Ilnickaya, & Minenok, 2018;Palao, & Valades, 2016). Shalayev (2007) notes that acrobatic exercises are one of the effective means of special training of athletes in volleyball.…”
Section: Introductionmentioning
confidence: 99%